Organizational Conflict Management In Islamic Education Perspective - Ehwanudin Ehwanudin Ehwanudin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2021)
The indicator that an organization or educational institution does not stagnate is the existence of appropriate conflict management in its management so that it can develop and achieve the goals of the organization effectively and efficiently. This requires good leadership, especially for a leader who must control conflict at a moderate level so that the organization becomes dynamic and achieves high effectiveness. If a conflict arises at the highest level, it is feared that the organization or educational institution will be difficult to control, even the most fatal thing is that the entire potential of educational institutions is used to find conflict solutions. This is what will harm educational institutions and can even fail to achieve common goals and objectives. The type of research in this study is a type of qualitative research and is library research. Therefore, due to the nature of this research is library research (library research). So the data collected and analyzed are entirely taken from literature and other documentation materials such as magazines, journals, and so on. This is where the role of organizational conflict management in the perspective of Islamic education is needed in discussing the concept of conflict management in education with sub-discussions: conflict and its problems, sources and types of conflict, the influence of conflict on educational institutions, and efforts to overcome conflict in Islamic education based on the Qur'an and Assunah.